The Abstract Book of the International Conference Populism in National and Global Media (24-25 November, 2023) - Šukaitytė, Renata (Vilnius University Proceedings, 2023)
The theme of the Conference − Populism in Local and Global Media − appeared naturally from the insightful observation of the rise of nationalist political discourses in media, citizens’ protests, and their views expression on social media, associated with major political events and campaigns - the COVID-19 pandemic, Russia’s war in Ukraine, and the dramatic economic setback in recent years. This situation was well exploited by a range of actors (media professionals, politicians, influencers, and celebrities) in their populist communication and rhetoric across different media channels. In the light of all these constellations and challenges in Europe and worldwide, an idea evolved to invite media scholars and practitioners to discuss the nexus between populism, politics, communication, media, and wider society. Thus, we were pleased to receive numerous insightful proposals by media and communication scholars from Lithuania and abroad and to hold this illuminating conference on the populist communication and the multiplicity of the populist discourses in media. The The Abstract Book includes the welcoming text by the organizers, the conference programme, the abstracts of the keynote panels, and the abstracts of the thematic paper panels.